Hubungan Pola Makan, Aktivitas, dan Kunjungan ANC dengan Kejadian Hiperemesis Gravidarum di BPM Bd. Kusmiyati: Correlation between Diet, Activity and ANC Visits with the Incidence of Hyperemesis Gravidarum in BPM Bd. Kusmiyati - Nur Dwiani Maulida (MPI Press, 2023)
Introduction: Excessive nausea and vomiting felt by pregnant women so that it interferes with activities or causes complications, this condition is called hyperemesis gravidarum. According to the theory, there are several causes, such as anemia, primigravida, psychosomatic (anxiety, depression, stress), heredity, human chorionic gonadotropin (HCG) factors, metabolism, allergies, infections, and diet Objectives: This study aims to determine the relationship and description of diet, activity, and ANC visits with the incidence of hyperemesis gravidarum in BPM Bd. Kusmiaty. Method: This study uses a quantitative descriptive analysis design with a cross-sectional approach. The population in this study were all pregnant women at BPM Ibu Kusmiyati consisting of 17 people in the first trimester and 33 in the second trimester. The technique for determining the sample in this study was total sampling using primary and secondary data. The analysis technique of testing the hypothesis data is by using Chi-Square Result: The results of this study indicate that the value of the relationship between activity and the incidence of hyperemesis gravidarum p-value is 0.030 <0.05. Value of the relationship between diet and ANC visits of pregnant women p-value (0.496). Conclusion: Activity associated with the incidence of hyperemesis gravidarum in BPM Bd. Kusmiyati. And there is no relationship between diet and ANC visits for pregnant women. However, the category of each variable is not a determinant of the degree of hyperemesis gravidarum experienced by pregnant women.